Trenching studies of active faults in Kamchatka, eastern Russia: Palaeoseismic, tectonic and hazard implications - Kozhurin, A; Acocella, V; Kyle, PR; Lagmay, FM; Melekestsev, IV; Ponomareva, V; Rust, D; Rovida, A; Sakharov, A; Tengonciang, A; Uy, H.; TIBALDI, ALESSANDRO; et al. (Tectonophysics, 2006)
The central part of the Kamchatka Peninsula is characterized by a well defined depression associated with active volcanism, aligned NE-SW. On the east, the depression is bounded by a prominent system of active faults known as the East Kamchatka Fault Zone (EKFZ). In order to improve understanding of the behaviour and kinematic role of this fault zone a fieldwork programme, including study of trenches, was conducted in the north-central part of this system. Aerial photograph analysis, ground-truthed, indicates a westward fault dip with predominantly normal slip, while lateral offsets of river terraces and stream channels demonstrate a combined dextral component. Over 20 excavated pits and natural exposures were examined to confirm a detailed tephra succession extending from the early Holocene to recent historic eruptions. This chronological framework then provided age control on five past faulting events recognised in three trenches. These events took place at about 10.5, 6.0, 4.5 and, in a two-event succession within a short time span, at 3.3-3.2ka BP. Event clustering may be characteristic and fault length-displacement values suggest earthquakes of M6.5, thus representing a significant new element in regional seismic hazard evaluations; additional to events generated at the subduction interface. The relatively long gap in faulting since the two most recent events may also be significant for hazard scenarios and there is a possible link between the faulting and volcanic activity in the depression. Overall, the EKFZ, together with the Nachiki Transverse Zone farther south, is thought to define a regional-scale block that is extending eastwards independently from the rest of Kamchatka. (c) 2006 Elsevier B.V. All rights reserved.